Research on Improvement of Characteristics of Ammonia Nitrate using Phosphate Rock and Potassium Chloride - Makhmudov Rafik Amonovich; Umurova Elnora Nozimovna (International Journal on Human-Computing Studies, 2021)
In this article, the results of research on improvement the composition and properties of ammonium nitrate using rock and potassium chloride - the most affordable potash product on the market as composite additives phosphate are given.